The Influence And Women'sempowerment Agency, Kaur Of Motivation And Leadership Style Onemployee Perform Ance In Family Planning District - Fachri Frasetya Fahlevi; Sulisti Afriani; Iswidana Utama Putra (Universitas Dehasen Bengkulu, 2023)
In achieving organizational goals, every organization needs resources to achieve them. These resources include natural resources, financial resources, scientific and technological resources, and human resources. This study aims to determine the effect of motivation and leadership style on employee performance at the Family Planning and Women's Empowerment Agency in Kaur Regency. The results of the study indicate a positive regression direction with the equation Y = 3.751 + 0.364X1 + 0.721 X2. Motivation has a significant effect on employee performance at the Family Planning and Women Empowerment Agency of Kaur Regency because the significant value is 0.004 which is smaller than 0.05. This illustrates that work motivation possessed by employees is able to improve employee performance. v Leadership style has a significant influence on employee performance at the Family Planning and Women Empowerment Agency of Kaur Regency because the significant value of 0.000 is smaller than 0.05. This illustrates that the better the leadership style, the employee's performance will also increase. Motivation and leadership style have a significant simultaneous influence on employee performance at the Family Planning and Women Empowerment Agency of Kaur Regency because the significant value of 0.000 is smaller than 0.05